Growing plants on oily, nutrient-poor soil using a native symbiotic fungus - Repas, Timothy S.; Gillis, D. Michael; Boubakir, Zakia; Bao, Xiaohui; Samuels, Gary J.; Kaminskyj, Susan G. W. (PLOS ONE, 2017)
The roots of land plants associate with microbes, including fungal symbionts that can confer abiotic stress tolerance. Bitumen extraction following oil-sand surface mining in the Athabasca region of Alberta, Canada removes plant nutrients but leaves a petrochemical residue, making the coarse tailings (CT) hostile to both plants and microbes. We isolated an endophyte strain of the Ascomycete Trichoderma harzianum we call TSTh20-1 (hereafter, TSTh) from a dandelion that was naturally growing on CT. TSTh colonization allowed tomato, wheat, and remediation seed mixtures to germinate and their seedlings to flourish on CT without the use of fertilizer. Compared to control plants, TSTh increased germination speed, percent germination, and biomass accumulation. TSTh also improved plant water use efficiency and drought recovery. TSTh-colonized plants secreted twice the level of peroxidase into CT as did plants alone. Over two months, plants colonized with TSTh doubled the petrochemical mobilization from CT over plants alone, suggesting a peroxide-mediated mechanism for petrochemical degradation. TSTh grew on autoclaved CT, bitumen, and other petrochemicals as sole carbon sources. Further, TSTh is a micro-aerobe that could metabolize 13C-phenanthrene to 13CO2 in 0.5% oxygen. TSTh has excellent potential for contributing to revegetating and remediating petrochemical contamination.